ANALYSIS OF FACTORS AFFECTING THE QUALITY OF PROFIT IN THE WOOD SUB-SECTOR AND ITS PROCESSING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Rimawan, Muhammad; Muniarty, Puji (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study aims to analyze the effect of likuidity, profitability, leverage, firm size and Investment Opportunity Set on earnings quality. The sampling technique was carried out using saturated sampling. The samples in this study are 4 companies in the wood and processing sub-sector that are listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The data in this study were processed using the SPSS application with multiple linear regression analysis methods. The hypothesis testing method uses a significance level of 5% or 0.05. The results showed that 1) the likuidity variable has an effect on earnings quality. 2) the profitability variable has no effect on earnings quality, 3) the leverage variable has an effect on earnings quality, 4) the firm size variable has an effect on earnings quality, and 5) the investment opportunity variable has an effect on earnings quality.6) the result silmultan has an effect earning quality